D대학 사례를 중심으로 한 전문대학 중도탈락 개선 방안 - 최길성(Kil Sung Choi); 이용창(Yong Chang Lee) (한국콘텐츠학회 논문지, 13(11), 2013)
It is becoming increasingly difficult for colleges to recruit new students to their full capacity. The increase of the withdrawal rate drives these colleges into crisis yet little has been done about it, because students with great possibility to withdraw enter colleges and old measures to stop them from dropping out hardly work. This study attempts to grope new measures to prevent dropout from college. To do this, I investigated withdrawal rate by college admission types and suggested measures to reduce withdrawal rate by incorporating the results of the investigation into admission procedures. I also compared the different types of admission in students satisfaction with college life and withdrawal rate, and suggested the measures to alleviated withdrawal rate. I expect the suggestions made in this study would be used effectively to reduce the withdrawal in colleges. 전문대학의 재학생 충원율은 갈수록 문제가 되고 있다. 특히, 중도탈락률의 증가는 전문대학을 심각한 위기로 몰고 있어도 속수무책인 상황이다. 왜냐하면, 중도탈락 가능성이 높은 학생들이 입학한 상태에서는 기존의 어떠한 방법도 중도탈락을 방지하기란 어렵기 때문이다. 따라서 본 연구는 중도탈락을 미연에 방지할 수 있는 새로운 방안을 모색하는데 목적을 두었다. 이를 위해 D대학의 입학전형별 중도탈락 실태를 파악한 후, 그 결과를 입학전형 방법과 절차에 반영함으로써 중도탈락을 개선하는 방법을 제시하였다. 또한, 입학전형별로 대학생활 만족도와 중도 탈락률 간 비교를 통해 중도탈락률을 개선하는 방법도 제시하였다. 본 연구에서 제안한 방법은 전문대학의 중도탈락률을 개선하는데 유효하게 적용될 것으로 기대한다.